Applied Linguistics in the Digital Age: Challenges and Opportunities - Athaya Fatihah Syauqiyah, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Starting from language, language is an arbitrary vocal symbol to communicate with each other. In other definition, language is the sounds that come out of the mouth even though mother tongue language, Indonesian language, English Language, etc. Language includes in science of linguistics which studies syntax, phonetic symbols and also morphology, Bilingualism, Multilingualism, etc. So, Applied Linguistics is a field of study that examines how language is used and how it can be improved in real-world contexts. It's an interdisciplinary field that draws on a variety of theoretical and methodological approaches from other disciplines, such as the humanities, social sciences, and natural sciences. In this modern era, technology plays an important role in contributing to the development of language and linguistics both in the community and in schools when especially in the classroom. But, technology in the Digital or modern era has many challenges and opportunities so it should reach a solution and how to overcome the challenges and also opportunities.